Outlander - Gabaldon, Diana (New York : Delacorte Press, 1991)
Hurtled back through time more than two hundred years to Scotland in 1743, Claire Randall finds herself caught in the midst of an unfamiliar world torn apart by violence, pestilence, and revolution and haunted by her growing feelings for James Fraser, a young soldier.
Imprint varies.
Keywords: Time travel -- Fiction; Culloden, Battle of, Scotland, 1746 -- Fiction; Jacobite Rebellion, 1745-1746 -- Fiction; Scotland -- History -- 18th century -- Fiction; Historical fiction; Fantasy fiction; Romance fiction